2006
DOI: 10.1200/jco.2005.01.9679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience With Intravenous and Oral Formulations of the Novel Histone Deacetylase Inhibitor Suberoylanilide Hydroxamic Acid in Patients With Advanced Hematologic Malignancies

Abstract: These results suggest that SAHA has activity in hematologic malignancies including HD and select subtypes of non-Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
264
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(276 citation statements)
references
References 15 publications
12
264
0
Order By: Relevance
“…Phase I-II clinical trials are underway or have been recently performed with SAHA in patients with advanced hematological malignancies, including MM [6][7][8][9][10][11][12][13]. Overall, these studies showed that SAHA was tolerable, although its toxicity profile was not negligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase I-II clinical trials are underway or have been recently performed with SAHA in patients with advanced hematological malignancies, including MM [6][7][8][9][10][11][12][13]. Overall, these studies showed that SAHA was tolerable, although its toxicity profile was not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Not unexpectedly, patients treated with SAHA for hematological malignancies experienced more grade 3-4 hematological toxicity than patients with solid tumors [6,14]. Thrombocytopenia occurring with SAHA was associated with the presence of hypolobular megakaryocytes, and not with an absolute reduction in the number of megakaryocytes [7]. This may raise the possibility that SAHA impairs megakaryocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vorinostat, a class I and II HDAC inhibitor, was approved more than 10 years ago for the treatment of CTCL [159]. Romidepsin, a pan-HDAC inhibitor, is also approved for use in CTCL patients as well as for relapsed and refractory PTCL.…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…64,[80][81][82] Also, Vorinostat and other HDIs have exhibited encouraging anti-cancer activity and relatively low patient toxicity in early clinical trials. [83][84][85][86][87][88][89] As a result, in October 2006, Vorinostat was approved by the FDA for treatment of cutaneous T-cell lymphoma (CTCL) in patients who have tried and failed other therapies (www.fda.gov/cder/Offices/OODP/whatsnew/ vorinostat.htm). Presumably, the encouraging clinical activity of Vorinostat is, at least in part, due to its preferential killing of transformed cells compared to primary cells.…”
Section: The Cellular Role Of Hp1 Proteinsmentioning
confidence: 99%